Childhood allergy is preceded by an absence of gut lactobacilli species and higher levels of atopy‐related plasma chemokines. (5th August 2020) - Björkander, S.; Carvalho‐Queiroz, C.; Hallberg, J.; Persson, J.‐O.; Johansson, M. A; Nussbaum, B.; Jenmalm, M. C; Nilsson, C.; Sverremark‐Ekström, E.
Summary: Alterations in the composition and reduced diversity of the infant microbiome are associated with allergic disease in children. Further, an altered microbiota is linked to immune dysregulation, including skewing of different T helper (Th) subsets, which is also seen in atopic individuals. The aim of this study was, therefore, to investigate the associations between gut lactobacilli and Th‐related plasma factors in allergy development during childhood. A total of 194 children with known allergy status at 1 year of age were followed to 10 years of age. We used real‐time polymerase chain reaction (PCR) to investigate the presence of three lactobacilli species ( Lactobacillus casei, L. paracasei, L. rhamnosus ) in infant fecal samples (collected between 1 week and 2 months of age) from a subgroup of children. Plasma chemokines and cytokines were quantified at 6 months and at 1, 2, 5 and 10 years of age with Luminex or enzyme‐linked immunosorbent assay (ELISA). Fractional exhaled nitrogen oxide (FeNO) was measured and spirometry performed at 10 years of age. The data were analysed by non‐parametric testing and a logistic regression model adjusted for parental allergy. An absence of these lactobacilli and higher levels of the chemokines BCA‐1/CXCL13, CCL17/TARC, MIP‐3α/CCL20 and MDC/CCL22 in plasma at 6 months of age preceded allergy development. The presence of lactobacilli associated with lower levels of atopy‐related chemokines during infancy, together with higher levels of interferon (IFN)‐γ and lower FeNO during later childhood. The results indicate that the presence of certain lactobacilli species in the infant gut may influence allergy‐related parameters in the peripheral immune system, and thereby contribute to allergy protection. Abstract : Detection of lactobacilli (L. casei, L. paracasei and L. rhamnosus) in feces during the first 2 months of life associates with reduced allergy‐prevalence and lower levels of atopy‐related chemokines in the first year(s) of life, and higher levels of IFN‐g and lower FeNO later in childhood. These associations between lactobacilli, allergy‐protection and the systemic immune profile were apparent also within the subgroup of children with double allergic heredity. The results indicate that the presence of certain lactobacilli species in the infant gut may influence allergy‐related parameters in the peripheral immune system, and thereby contribute to allergy‐protection.